Forms of Economic Development Community at Islamic Boarding School - Achmad Faishal (The International Journal of Politics and Sociology Research, 2021)
Community development is one of the methods of social work where the locus and main goal is to improve the quality of people's living standards by utilizing the potential or resources they carry. While the pesantren which is identical with the ideal place to seek or explore the religious sciences is also part of one of the active institutions and has the potential to be used as the basis or driving force for the change agenda, in pesantren, of course, not only religious sciences are taught but also as well as social sciences that are directly related to their lives. In building the community's economy, there is an assumption that in order to achieve economic equality, economic growth must be preceded, then distributed through the trickle down effect. because if not then what happens is the distribution of poverty. To spur economic growth, BPM-PP Annuqoyah guluk-guluk Sumenep Madura orientated its efforts to build a community-based economic sector, home industries, livestock, plantations, to cooperatives as well as shops, all of which are real sectors that BPM-PP Annuqyah is trying to develop. With a strong principle that is participatory (pesantren and community) economic development can be in line with what is expected, Islamic boarding schools get benefits, people earn income, of course with this kind of economic development model can make PP Annuqoyah and the community more communicative. This study aims to determine the forms of economic development of the community around the Islamic boarding school, conducted by the PP Community Service Agency (BPM). Annuqoyah Guluk-guluk Sumenep Madura. The results obtained from this study are that; economic development that has been carried out by BPM PP. The annuqoyah is not only for the internal circles of the pesantren, but specifically to help the community's economy, which is also known as Community Development.